Struktur Kepemilikan Keluarga dan Kinerja Perusahaan di Sektor Barang Konsumsi pada Periode 2010-2015 - Francisca Ivana; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
This study aimed to investigate the effect of family ownership toward firm performance. Control variables used were good corporate governance, competitive intensity, and firm age. The sample consisted of 30 consumer goods companies, listed in Indonesian Stock Exchange (IDX) between the periods of 2010-2015. Analysis was done by using multiple linear regression and processed in SPSS 23. The results showed that family ownership, good corporate governance, and competitive intensity had significant positive relationship on firm performance, while firm age had no significant influence.